Penerapan arsitektur ikonik pada perancangan Museum Kapal Pinisi di Kabupaten Bulukumba - Yusdar, Annisa; As, Zulkarnain; Ibrahim, Ahmad (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
The Pinisi ship is one of the masterpieces and symbols of the Bulukumba community, known as Butta Panrita Lopi or the region inhabited by people who are experts in making Pinisi ships. Although the Pinisi ships from Bulukumba are well-known internationally, the region still faces challenges in promoting and preserving its cultural heritage. This study aims to design a Pinisi Ship Museum by applying iconic architecture principles. This serves as an option to introduce and preserve the cultural heritage of the Pinisi ship, and the museum is expected to become a new icon in Bulukumba Regency. The research method used includes field surveys to collect primary data on the physical environmental conditions of the location, and descriptive methods such as literature review and precedent studies to gather data and examples of buildings related to the design concept. The results show that the iconic architecture applied to the design of the Pinisi Ship Museum incorporates the philosophy of the elements that form the Pinisi ship into the building design. The application of iconic architecture for the Pinisi Ship Museum in Bulukumba Regency results in a unique form that portrays the grandeur of a building, making it a new icon in Bulukumba.